Lung volumes, gas transfer and oscillometry after preterm birth: systematic review and meta-analysis - James T.D. Gibbons; Michael L. Beaven; Christopher W. Course; Sarah J. Kotecha; Thomas Hixson; Melissa Zuidersma; Andrew C. Wilson; Sailesh Kotecha; Shannon J. Simpson (European Respiratory Review, 2025)
Background Small airway and lung parenchymal abnormalities frequently occur following preterm birth but are commonly missed by spirometry. Static lung volumes, diffusing capacity of the lung for carbon monoxide (DLCO) and oscillometry provide a more precise characterisation of these conditions. We hypothesised that differences in these measures exist between individuals born preterm and at term and we aimed to systematically review the literature to identify and quantify these differences in lung function. Methods This systematic review and meta-analysis, registered with PROSPERO (CRD42022320775) and guided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards, searched six databases up to 29 December 2024. We included studies comparing lung function between preterm subjects and term controls via static lung volumes, gas transfer or oscillometry. Differences in lung function were analysed using random-effects meta-analysis to compute the standardised mean difference (SMD). Results From 12 143 titles, we analysed 52 cohorts with static lung volumes, 37 with gas transfer and 18 with oscillometry data. While total lung capacity was similar between preterm and term cohorts (SMD −0.08, 95% CI −0.17 to 0.004), preterm participants showed increased residual volume (SMD 0.32, 95% CI 0.19 to 0.44) and residual volume/total lung capacity (SMD 0.45, 95% CI 0.28 to 0.63). DLCO was lower in preterm cohorts (SMD −0.51, 95% CI −0.64 to −0.38). Preterm cohorts also demonstrated increased airway resistance at 5/6 Hz (SMD 0.44, 95% CI 0.22 to 0.67), difference between airway resistance at 5/6 Hz and 20 Hz (SMD 0.51, 95% CI 0.07 to 0.96), resonant frequency (SMD 0.63, 95% CI 0.12 to 1.15) and area under the reactance curve (SMD 0.62, 95% CI 0.35 to 0.88). Interpretation We demonstrate that preterm birth is linked to notable abnormalities in static lung volumes, gas transfer and oscillometry, underscoring the necessity of employing comprehensive pulmonary function tests beyond spirometry to monitor and address long-term respiratory outcomes effectively.